Novel low-temperature synthesis of nanosized NiZn ferrite - Verma, S.; Pradhan, S. D.; Pasricha, R.; Sainkar, S. R.; Joy, Pattayil Alias (Journal of the American Ceramic Society, 2005)
Nanosized NiZn ferrite powder is synthesized by a low-temperature method, using a unique combination of citric acid and glycine. An appropriate molar ratio of both citric acid and glycine offers a low-temperature synthetic route by incorporating the complexation behavior of citric acid and the combustion nature of glycine. Thermal decomposition/controlled autocatalytic combustion of the composite gel occurs at a low temperature of around 175 degrees C, with the evolution of a large amount of gases. Transmission electron microscopic studies showed that the average particle size of the ferrite obtained is similar to 2.5 nm, with a narrow size distribution. Uniformly distributed fine-grained microstructure with low porosity is obtained for a sample sintered at 1000 degrees C.

Study of correlation of structural and surface properties with electrochemical behaviour in carbon aerogels - Hebalkar, Neha; Arabale, G.; Sainkar, S. R.; Pradhan, S. D.; Mulla, Imtiaz S.; Vijayamohanan, K.; Ayyub, P.; Kulkarni, S. K. (Journal of Materials Science, 2005)
Carbon aerogel is a promising material for electrochemical double layer capacitors. In this paper carbon aerogels prepared by subcritical drying method are investigated for the change in the structure and surface properties at different pyrolysis temperatures. The important relations between structure, morphology, surface area and electrical properties were studied using X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), surface area measurement and cyclic voltametry. It is shown that structure and the surface functional groups play important role in enhancement of electrochemical capacitance. The specific capacitance achieved was 114 F/gm which is quite large value for subcritically prepared carbon aerogels without any kind of activation process. (c) 2005 Springer Science + Business Media, Inc.

Adsorption of octadecyltrichlorosilane on mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Sawant, Dhanashri P.; Jacob, Nalini E.; Patil, K. R.; Gaikwad, A. B.; Pradhan, S. D. (Applied Surface Science, 2006)
Adsorption of octadecyltrichlorosilane (OTS) on mesoporous SBA-15 has been studied by using Brunauer-Emmett-Teller (BET) surface area analysis, scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDAX), Fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS) and thermo-gravimetric analysis (TGA) techniques. BET surface area analysis shows decrease of surface area from 930 to 416 m(2)/g after OTS adsorption. SEM pictures show close attachment of SBA-15 particles. EDAX measurements show increase of carbon weight percentage and decrease of oxygen and silicon weight percentage. XPS results closely support EDAX analysis. FTIR spectra shows presence of methyl (-CH3) and methylene (-CH2) bands and oriented OTS monolayer on SBA-15. Thermo-gravimetric analysis shows that the OTS adsorbed on SBA-15 are stable up to a temperature of 230 degrees C and that the OTS monolayers decompose between 230 and 400 degrees C. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Adsorption; OTS; SBA-15; Self-assembly; thermal stability